Molecular and immunological characterization of cysteine protease from Phaseolus vulgaris and evolutionary cross‐reactivity. Issue 9 (20th May 2022) - Sharma, Akansha; Vashisht, Srishti; Mishra, Richa; Gaur, Shailendra Nath; Prasad, Nagendra; Lavasa, Shakuntala; Batra, Janendra Kumar; Arora, Naveen
Abstract: A commonly consumed legume in India, the kidney bean ( Phaseolus vulgaris ) is associated with allergy. We report molecular and immunological characterization of cysteine protease allergen and its cross‐reactivity. In silico allergenicity assessment and phylogenetic analysis of kidney bean cysteine protease showed significant sequence homology (upto 67%) with allergens from kiwi, papaya, soybean, ragweed pollen and mites. Physicochemical properties and motif‐analysis depicted cysteine protease as probable allergen. Multiple sequence alignment and phylogenetic analysis indicated structural conservation between kidney bean and homologous cysteine protease sequences. The gene was cloned, expressed and affinity purified. Cysteine protease was resolved at 42 kDa and exhibited high IgE binding (up to 89%) with hypersensitive sera. Cysteine protease showed functional property on cross‐linking IgE receptors and upregulated expression of CD203c on activated basophils. In inhibition studies, 8.4 ng of cysteine protease was required for 50% self‐inhibition, whereas significant inhibition was also observed with kidney bean (52 ng), black gram (155 ng), chick pea (437 ng), mesquite pollen (36 ng), house dust mite (64.85 ng), Alternaria alternata (78.8 ng) and Curvularia lunata (73.6 ng) extracts. ConSurf analysis indicated conserved active site and catalytic residues in mature domain among proteases from legumes, fruits, pollens, mites and fungus. In summary, P. vulgaris cysteine protease was molecularly characterized having functional activity. This study demonstrated, cross‐reactivity between food and aeroallergens based on evolutionary conservancy that showed its clinical importance as cross‐reactive allergen. Practical applications: Adaptation of sustainable lifestyle has led to a surge in consumption of plant‐based foods especially legumes. Their high nutritional content lowers the risk of developing cardiovascular diseases, diabetes, obesity, and stroke. Kidney beans, a commonly consumed legume in Indian subcontinent, have a potential to be used as nutraceutical and functional food. Despite its alimentary nature, it elicits allergic reactions. Being a major sensitizer, trivial information regarding its allergic components has led to an urgent need for exploring its allergen repertoire. Our study reported biochemical and immunological characterization of its major cysteine protease allergen. Cysteine proteases are major cross‐reactive allergens from insects, fruits and fungal sources. Identification and molecular characterization of such immunodominant allergens by RDT offers the prospect of using recombinant proteins for accurate diagnosis and therapeutic purposes. This study suggests that a potential major cross‐reactive allergen may aid in developing allergy management interventions for a wide range of allergenic sources. Abstract : Kidney bean cysteine protease was characterized as a major cross‐reacting allergen by in silico and in vitro methods. In computational assessment cross‐reactivity and allergenicity of allergen was determined using sequence homology approach. This was followed by cloning and purification of allergen using recombinant DNA technology and affinity chromatography, respectively. Finally, in vitro analysis using food hypersensitive patients' sera validated in silico data, thereby representing cysteine protease as a potential allergen.